2020
DOI: 10.3390/cells9061369
|View full text |Cite
|
Sign up to set email alerts
|

Resistin Enhances VCAM-1 Expression and Monocyte Adhesion in Human Osteoarthritis Synovial Fibroblasts by Inhibiting MiR-381 Expression through the PKC, p38, and JNK Signaling Pathways

Abstract: The development of osteoarthritis (OA) is characterized by synovial inflammation and the upregulation of vascular cell adhesion molecule type 1 (VCAM-1) in human osteoarthritis synovial fibroblasts (OASFs). This increase in VCAM-1 expression promotes monocyte adhesion to OASFs. The adipokine resistin is known to promote the release of inflammatory cytokines during OA progression. In this study, we identified significantly higher levels of resistin and CD68 (a monocyte surface marker) expression in human OA tis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 43 publications
1
25
0
Order By: Relevance
“…Leptin augments levels of IL‐6 and IL‐8 in human synovial fibroblasts 34,35 . Resistin has been shown to increase angiogenesis and monocyte infiltration during arthritis progression 21,36 . However, it is unclear as to what role resistin plays in inflammatory cytokine production during OA disease.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Leptin augments levels of IL‐6 and IL‐8 in human synovial fibroblasts 34,35 . Resistin has been shown to increase angiogenesis and monocyte infiltration during arthritis progression 21,36 . However, it is unclear as to what role resistin plays in inflammatory cytokine production during OA disease.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously reported that in male Sprague‐Dawley (SD) rats with ACLT‐induced OA, blocking resistin activity ameliorated disease severity by preventing ACLT‐induced effects on subchondral bone architecture and histological changes in resistin and monocyte expression 21 . Of the wide variety of animal models of that are available for studying the pathogenesis of OA, none can be fully extrapolated to the human condition of OA; the data suggest that different models relate to particular subtypes of OA, with distinct molecular mechanisms in joint structural damage and pain that depend on how OA is induced 37 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, resistin up-regulates the expression of chemokines (i.e., CCL2, CCL3, CCL4, CCL5, CXCL1, and CXCL2) via transcription factors NF-kB and C/EBPb in human articular chondrocytes (100). It enhances VCAM-1 expression and monocyte adhesion through the PKC, p38, and JNK signaling pathways in human osteoarthritis synovial fibroblasts (103). In endothelial cells, resistin up-regulates ICAM-1, VCAM-1, fractalkine, and MCP-1 via TLR4, JNK/p38, AP-1, and NF-kB dependent pathways or by Gi/o signaling pathway (104)(105)(106)(107)(108).…”
Section: Chemotactic Activitymentioning
confidence: 99%